Frankenstein, or, The modern Prometheus - Grimly, Gris (Balzer + Bray, 2013)
Retells, in graphic novel format, Mary Shelley's classic tale of a monster, assembled by a scientist from parts of dead bodies, who develops a mind of his own as he learns to loathe himself and hate his creator.